An exploration of possible KING-IV implementation challenges relating to remuneration disclosures - Anyango, Dianne (My University, 2017)
With the high income disparity that South Africa faces coupled with the major corporate scandals that have recently occurred, regulators and institutional investors are paying increased attention to both the disclosure and ‘shareholder say’ on remuneration. Therefore this has resulted in remuneration being one of the major governance developments that King-IV code addresses. It has, therefore, become imperative for companies to start looking at remuneration as an important corporate governance tool that aids in fostering increased accountability amongst management. Some of the concerns that are raised regarding the new disclosure requirements include; how some of the requirements will be defined and to what extent disclosure is required by companies, how will the disclosure then be assessed and analyzed and finally what the norm will be in comparison to competitor disclosures. Therefore, the aim of this thesis is to examine what some of the implementation challenges that corporations will face when applying the disclosure requirements of King-IV. Using detailed interviews, this will be one of the few papers that uses the views of respondents as a primary source of data. By assessing the views of both technical experts and preparers regarding their perceptions of the various challenges that will be encountered when applying the principles of the code. As the King-IV code recently became effective this research will be amongst the first few papers on King-IV and adding to the existing body of corporate governance research. Furthermore, this thesis aims at providing a practical contribution by providing preparers of annual reports the first set of challenges expected when practically applying the disclosure requirements the King-IV.
University of the Witwatersrand In partial fulfilment of the requirements for the degree Master of Commerce, 2017
Keywords: Wage payment systems; Financial statements--Standards; Wages--Management